The Arrowheads of the Squared-Mouthed-Pottery Culture: Reconstruction and Shooting Experiment - Maddalena Sartori (EXARC Journal, 2019)
This international experimental project focused on the production of replicas of different models of flat-retouched flint arrowheads (stemmed, with flat base, and ogives -with rounded base-) in use within the Neolithic Squared-Mouthed-Pottery Culture (SMP) of Northern Italy. The aim was to test their efficiency in order to understand if different morphologies of points produce different effects on the target. During the experimentation, an average penetration rate between 5 and 10 cm was registered. Both the models with a stem (“Italian type”) and those with flat base (used north of the Alps) are efficient, so it is supposed that their adoption could be due to cultural factors. On the other hand, none of the “ogives” remained stuck in the target, suggesting their interpretation should be considered as a preformrather than an arrowhead. The impact fractures registered on the replicas mostly have an oblique morphology that does not affect the re-use of the arrowhead.